Coorg - Revised Plan - Government of Karnataka (Government of Karnataka, 1955)
The Revised Second Five-Year Plan for Coorg State (1956-61) outlines a comprehensive strategy for socio-economic development through targeted investments in agriculture, irrigation, power supply, industry, education, health, and infrastructure. With a proposed total expenditure of Rs. 412.81 lakhs, the plan emphasizes intensive cultivation and crop development, minor irrigation schemes such as the Lakshmanathirtha Project, and rural electrification. Industrial initiatives focus on small-scale and cottage industries alongside the establishment of training centers for skill development. Social services, including education and health, receive substantial allocations to enhance accessibility and quality, with particular attention to the welfare of scheduled tribes, castes, and backward classes. The accompanying financial planning document details capital and recurring expenditures, revenue sources, manpower requirements, and material allocations, highlighting a strategic phasing of investments over five years. With meticulous planning for administrative, technical, and unskilled labor, and allocation of essential materials like cement, steel, timber, and bricks, the plan ensures effective project implementation. The integrated approach underscores holistic regional development, leveraging data-driven decisions, careful resource management, and sustained monitoring to align infrastructure and social services with community needs. Overall, the plan serves as a blueprint for balanced growth, emphasizing efficiency, sustainability, and comprehensive improvement of Coorg’s economic and social landscape.
Revised Draft Second five-year Plan
Revised Draft Second five-year Plan
Keywords: Coorg State; State Plan; Agriculture Development; Irrigation Projects; Power Supply; Industry Promotion; Social Services; Education Enhancement; Health Infrastructure; Road Construction; Financial Planning; Manpower Allocation